INTERNALISASI KURIKULUM BERBASIS CINTA (KBC) PERSPEKTIF KI HADJARDEWANTARA: MANIFESTASI KEADILAN EPISTEMIS DAN MODERASI BERAGAMA DALAM PAI - I'anatul Mufarikhah (Jurnal Manajemen Pendidikan, 2026)
This study aims to conceptualize the internalization of the LoveBased Curriculum (KBC) in Islamic Religious Education (PAI) learning through the philosophical lens of Ki Hadjar Dewantara. The main focus of the study is formulated to examine how the synthesis of these two concepts can manifest epistemic justice for learners while strengthening the values of religious moderation within educational environments.Methods: This study is a library research project employing a philosophical-hermeneutic approach. Data were collected from various primary and secondary sources related to KBC, Ki Hadjar Dewantara’s pedagogical texts (particularly the Among System), and documents on strengthening religious moderation. Data analysis was conducted using content analysis techniques and deductive theoretical synthesis.Results: The findings indicate that the internalization of KBC based on Ki Hadjar Dewantara’s thought transforms the PAI paradigm from indoctrinative to emancipatory. The value of *rahmah* (compassion) in KBC, synergized with the principles of *Asih*, *Asah*, and *Asuh* in the Among System, has been shown to provide space for the diversity of students’ perspectives (epistemic justice) and to organically foster tolerant, inclusive, and balanced (*wasathiyah*) attitudes as the primary foundation of religious moderation.Novelty: The novelty of this study lies in the reconstruction of a contemporary PAI curriculum that integrates theological values (KBC) with the roots of Indonesian cultural pedagogy (KHD’s Among System), specifically to address the problem of epistemic injustice in religious classroom